Avaliação do programa de proteção a crianças e adolescentes ameaçados de morte do estado do Ceará (PPCAAM/CE) à luz da proteção integral - Paula, Ana Camila Ribeiro de (2023)
The theme of lethal violence against children, adolescents and young people is recurrent in the 2000s, mainly against those who are poor, black and residents of the peripheries. The Program for the Protection of Children and Adolescents Threatened with Death (PPCAAM) emerged in 2003, as an initiative of the Federal Government, in order to protect children and adolescents from death threats and, thus, combat the high mortality rates of children and teenagers. This evaluative research is intended to evaluate the PPCAAM of the State of Ceará in the light of integral protection. With the objective of evaluating how the PPCAAM/CE acts in the protection of adolescents and young people threatened with death, I conducted my investigative look to understand the context of violence and violations of rights that make young people, mostly black and in a condition of poverty multidimensional, preferred victims of murders in Ceará. I sought to apprehend the actions planned and executed by the PPCAAM/CE, in order to understand how the protection of lives that enter the program takes place. I prioritized the adoption of qualitative research methods, in order to enable the construction of analytical categories in their historical and dialectical process. I seek, therefore, to produce a counter-hegemonic evaluation, from the perspective of in-depth evaluation, with the contributions of applied social research, based on ethical values. With emphasis on the analysis of context and content of public policy for children, adolescents and young people, in the particularities of PPCAAM/CE. In addition to understanding how death threats to adolescents and young people are present in Brazilian society and, in particular, in Ceará. Finally, I emphasize that the protection guaranteed in the PPCAAM/CE is protection against death, and not full protection, in view of the limits of the program itself. There is an attempt to guarantee the family and community coexistence of the protected ones, but with the process of deterritorialization these bonds are weakened and/or broken. It is necessary to build another research agenda that takes into account other perspectives that this research did not explore, such as the view of those who are under protection. PPCAAM protects lives, and every life protected matters. This time, it is an indispensable program that needs to be strengthened and improved.